2017
DOI: 10.1371/journal.pone.0187760
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of intestine microRNAs and targets in red swamp crayfish, Procambarus clarkii infected with white spot syndrome virus

Abstract: MicroRNAs (miRNAs) are small non-coding endogenous RNA molecules that play important roles in the innate immunity system of invertebrates, especially in the aspect of antivirus. In the present study, high-throughput small RNA Illumina sequencing systems were used to identify differentially expressed miRNAs (DEMs) from the intestines of Procambarus clarkii that were infected with white spot syndrome virus (WSSV). As a result, 39 known and 12 novel miRNAs were identified in both NG and WG small RNA libraries. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, miRNAs have emerged as novel regulatory of the actin cytoskeleton, via the regulation of cell growth and motility [ 42 , 43 ]. For example, miR-146a targets ROCK1 which affects cell movement in androgen-independent prostate cancer [ 44 ]; miR-155 is associated with TGF-induced RhoA suppression, leading to the dissolution of tight junctions between cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miRNAs have emerged as novel regulatory of the actin cytoskeleton, via the regulation of cell growth and motility [ 42 , 43 ]. For example, miR-146a targets ROCK1 which affects cell movement in androgen-independent prostate cancer [ 44 ]; miR-155 is associated with TGF-induced RhoA suppression, leading to the dissolution of tight junctions between cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression profile of miRNAs changed a lot in pathological state or environmental factor stimulation. Previous studies have reported the miRNA profiles in P. clarkia, for example, Wang et al and Du et al identified the miRNAs in gills, intestines and lymph organs of P. clarkia infected with white spot syndrome virus [13][14][15]. Ou et al screened the miRNAs potentially related to immunity against Spiroplasma eriocheiris infection in P. clarkia [16].…”
Section: Introductionmentioning
confidence: 99%